Combining the Heatpipe Reformer technology with hydrogen-intensified methanation for production of synthetic natural gas. (1st May 2018) - Leimert, Jonas M.; Neubert, Michael; Treiber, Peter; Dillig, Marius; Karl, Jürgen
Graphical abstract: Highlights: Overview on chemistry and advantages of hydrogen-intensified methanation. Proof-of-concept for hydrogen-intensified methanation coupled with Heatpipe Reformer. Reforming of higher hydrocarbons allows the production of a tar-free product gas. Improvement of methane yield due to hydrogen addition. Energy balance for the concept derived from the experimental results. Abstract: Recent developments in the energy sector require a combination of renewable carbon sources (e.g. biomass) and water electrolysis as a basis for electrical energy storage. While many approaches concentrate on the usage of hydrogen from electrolysis with CO 2 for the generation of second generation fuels like synthetic natural gas, the presented paper introduces a combination with the Heatpipe Reformer biomass gasification process: This process produces a synthesis gas, which can be fully and directly converted to methane using additional hydrogen produced in an electrolyser. Furthermore, the applied nickel catalyst is able to convert higher hydrocarbons in the syngas, increasing methane yield and resulting in higher process efficiencies and no additional scrubbing for the adaptation of the CHO stoichiometry is necessary. The Heatpipe Reformer also allows pressurized gasification, which is beneficial for a subsequent methanation step. The full process chain including a 100 kW gasifier and a bench scale methanation reactor was operated in a test campaign for approx. 20 h at different pressure levels. This paper presents results from the process of gasification and methanation as well as the conversion of higher hydrocarbons. An energy balance finally evaluates the entire process in terms of efficiency.